2018
DOI: 10.2147/ott.s161311
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CLEC3A promotes tumor progression and poor prognosis in breast invasive ductal cancer

Abstract: IntroductionThe aim of this study was to evaluate the expression of C-type lectin domain family 3 member A (CLEC3A) and its clinical significance in breast invasive ductal cancer (IDC) as well as its effect on breast cancer (BC) cell proliferation and metastasis. In this study, the level of CLEC3A expression in The Cancer Genome Atlas (TCGA) datasets was analyzed.Materials and methodsClinical collected samples and BC cells were measured using quantitative reverse transcription polymerase chain reaction. Its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…CLEC3A expression has also been reported in breast cancer tissue and high CLEC3A expression significantly correlated with poor prognosis. A previous study indicated that CLEC3A promotes invasion and metastasis of breast cancer cells by activating the PI3K/Akt signaling pathway …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CLEC3A expression has also been reported in breast cancer tissue and high CLEC3A expression significantly correlated with poor prognosis. A previous study indicated that CLEC3A promotes invasion and metastasis of breast cancer cells by activating the PI3K/Akt signaling pathway …”
Section: Discussionmentioning
confidence: 99%
“…Referring to the previous studies, CLEC3A, MMP7, and LCN2 could play roles in tumor cell migration through the pathway as shown in Figure . Briefly, PI3K/AKT signaling pathway, activated by CLEC3A and other molecules, upregulates MMP7 and LCN2 thorough loss of PKP3, which promotes cell migration (Figure A). CLEC3A is also located in cell membrane, and support adhesion between tumor cells by interacting with Extracellular matrix (ECM) on the cell surface .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…clec-2, a member of the c-type lectin family, was highly expressed in clear cell renal cell carcinoma and was positively associated with poor patient prognosis (21) and it was also observed to regulate cell proliferation and migration (22). clec3a, another c-type lectin, was reported to be highly expressed in breast invasive ductal carcinoma and promoted breast cancer cell proliferation and migration (8). a previous study has demonstrated that clec3a is involved in bone formation (23); however, the effect of clec3a on oS cells is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional C-type lectins have been reported in various pathological states, including cancer; for example, Wang et al (7) observed that c-type-lectin-like-2 promoted the proliferation and migration of gastric cancer cells by regulating the aKT signaling pathway. ni et al (8) demonstrated that high expression levels of the c-type lectin domain family 3 member a (clec3a) were positively associated with poor prognosis in patients with invasive ductal carcinoma of the breast. in addition, as a member of the c-type lectin superfamily, CLEC3A was originally identified in cartilage, and a previous study reported that clec3a was involved in bone formation (6); however, the effect and molecular mechanism of clec3a in oS is largely unknown.…”
Section: Suppression Of Clec3a Inhibits Osteosarcoma Cell Proliferatimentioning
confidence: 99%